1989
DOI: 10.1177/039139888901200403
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Features of Dialysis Amyloid Spondyloarthropathy

Abstract: Nine patients undergoing regular dialytic treatment (RDT) for more than 60 months (mean 125 +/- 33 months) showed clinical and radiological evidence of non-infective destructive spondyloarthropathy (DSA). The cervical spine was the skeletal segment most affected (100% of cases). Three patients were found also to be suffering from discal and bone alterations of the dorsal column, and in two other patients the vertebral bodies L4-L5 were changed. Typical radiological pictures showed a narrowing of intervertebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…A chronic arthropathy that predominantly involves the shoulders and is frequently associated with amyloid carpal tunnel syndrome (CTS), subchondral bone cysts or erosions, and destructive arthropathies has recently been described in such patients (2). The cervical spine is frequently involved in this erosive process, and there are numerous reports of a destructive spondylarthropathy of the cervical spine (3)(4)(5)(6)(7)(8)(9)(10). However, the craniovertebral junction has not been extensively investigated, despite the risk of severe neurologic complications associated with lesions at this site.…”
mentioning
confidence: 99%
“…A chronic arthropathy that predominantly involves the shoulders and is frequently associated with amyloid carpal tunnel syndrome (CTS), subchondral bone cysts or erosions, and destructive arthropathies has recently been described in such patients (2). The cervical spine is frequently involved in this erosive process, and there are numerous reports of a destructive spondylarthropathy of the cervical spine (3)(4)(5)(6)(7)(8)(9)(10). However, the craniovertebral junction has not been extensively investigated, despite the risk of severe neurologic complications associated with lesions at this site.…”
mentioning
confidence: 99%
“…Fiocchi et al [3] reported 18.0% (9 of 50 patients) and Leone et al [8] reported 19.4% (6 of 31 patients). In our study [20], the incidence of DSA was 20.8% (123 of 616 patients) and almost corresponded to the former studies.…”
Section: Discussionmentioning
confidence: 97%
“…The pathogenesis and natural history of DSA are still not fully understood, but it is a well-known amyloidosis, which consists of b2-microglobulin and plays an important role in the development of DSA [2,3,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been pro-(small arrows), displacing the pharyngeal air. chi and colleagues (10). Reports of an associated fracture of the dens and quadriplegia secondary to extradural compression by Pzm demonstrate the serious nature of this process (13).…”
Section: Discussionmentioning
confidence: 99%